The Effect of Choice-Making as an Intervention for Problem Behavior: A Meta-Analysis - Shogren, Karrie A.; Faggella-Luby, Michael N.; Sung Jik Bae; Wehmeyer, Michael L. (Journal of positive behavior interventions, 2004)
Supporting people with disabilities in expressing preferences and making choices is a core value in positive behavior support. Indeed, in recent years, the field has increasingly focused its attention on the importance of making choices and the potential benefits of choice-making opportunities in enhancing the quality of life of people with disabilities. In addition, an emerging database is suggesting that providing opportunities to make choices can serve as an intervention for decreasing problem behavior. The authors of this article examine the efficacy of the use of choice-making as an intervention for reducing problem behavior through a meta-analysis of single-subject research studies using choice-making as an intervention. A search of the PsycINFO and ERIC databases yielded 13 studies that met the meta-analysis criteria, with interventions affecting 30 participants. The impact of choice interventions was evaluated using the percentage nonoverlapping data and percentage zero data metrics. Overall, providing choice opportunities resulted in clinically significant reductions in the number of occurrences of problem behavior. The authors discuss the benefits of utilizing choice as an intervention and provide future directions for research in this area.